Rezidivfreies Überleben nach radikaler Prostatektomie und PDE-5-Hemmer-Einnahme - Hofer, Luisa; Radtke, Jan Philipp; Rapp, Carmen; Pahernik, Sascha; Teber, Dogu; Hohenfellner, Markus; Hadaschik, Boris (Der Urologe, 2017)
Background: Phosphodiesterase type 5 (PDE-5) inhibitors are widely used for penile rehabilitation and treatment of erectile dysfunction after radical prostatectomy. Recently, Michl et al. showed in a monocentric, retrospective and non-randomized analysis that PDE-5 inhibitors may cause higher biochemical recurrence rates after radical prostatectomy. This unexpected and serious adverse side effect of PDE-5 inhibitors was scrutinized on the basis of patients in our prospective tumor database.Materials and methodsWe included 358 patients after radical prostatectomy with bilateral nerve-sparing and without neo- or adjuvant therapy during 2004 and 2015. In all, 65.9% of the patients regularly took PDE-5 inhibitors postoperatively, 34.1% did not. Patients with sporadic use were excluded from the primary analysis. We used Kaplan-Mayer analysis to compare biochemical recurrence rates in both groups (endpoint: PSA > 0.2 ng/ml or salvage therapy).ResultsBoth groups showed comparable clinical parameters. There was no significant difference in recurrence-free survival (p = 0.9334): 60 months postoperatively 90.4% of men with PDE-5 intake vs. 90.8% of men without intake of PDE-5 inhibitors were recurrence-free.ConclusionAlthough our analysis was constructed similar to the analysis of Michl et al., we could not confirm their results. Taken together with recent cohort study from Scandinavia, postoperative prescription of PDE-5 inhibitors seems to be safe and should be discussed with patients.